Language and minority rights ethnicity, nationalism and the politics of language - May, Stephen 1962- (Routledge, 2012)
"The first edition of Language and Minority Rights, an outstanding interdisciplinary analysis of the questions and issues concerning minority language rights in modern nation-states, is now regarded as a key benchmark in the field of language rights and language policy. Its core arguments have shaped the discussion of language rights over the last decade. This new edition substantially revises and updates this provocative and groundbreaking book, addressing new theoretical and empirical developments since its initial publication, including the burgeoning influence of globalization and the relentless rise of English as the current world language. Stephen May's broad position, however, remains largely unchanged. He argues that the causes of many of the language-based conflicts in the world today still lie with the nation-state and its preoccupation with establishing a 'common' language and culture via mass education. The solution, he suggests, is to rethink nation-states in more culturally and linguistically plural ways while avoiding, at the same time, essentializing the language-identity link. This new edition, like the first, adopts a wide interdisciplinary framework, drawing on sociolinguistics, applied linguistics, sociology, political theory, education and law."